(untitled) (The Journal of Geography Education in Africa, 2018)
The purpose of this article is twofold. Firstly, to affirm the establishment of the Southern African Geography Teachers’ Association (SAGTA) and the Journal of Geography Education for Southern Africa (JoGESA) , and secondly, to comment on how these two partner organisations can (and should) play a role in strengthening and advancing geography education in South Africa and further afield. The key challenges facing geography education in South Africa are also discussed. These include the strength of its scholarly voice, the state of school geography and teacher education. The article raises key questions and makes some suggestions of how they could be addressed in relation to the work of these two organisations. The insights provided by this article may provide talking points that help to set an agenda for strengthening and enhancing Southern African geography education.